Single Center Outcome of Multiple Births in the Premature and Very Low Birth Weight Cohort in Singapore - Anand, Amudha Jayanthi; Sabapathy, Karthik; Sriram, Bhavani; Rajadurai, Victor Samuel; Agarwal, Pratibha Keshav (American Journal of Perinatology, 2020)
Objective The aim of this study is to compare neonatal mortality and morbidity in multiple and singleton preterm/very low birthweight (PT/VLBW) multiethnic Asian infants.Study Design Cohort study of 676 singleton and 299 multiple PT/VLBW infants born between 2008 and 2012 at KK Women's and Children's Hospital, the largest tertiary perinatal center in Singapore with further stratification by gestational ages 23 to 25 (Group 1), 26 to 28 (Group 2), and ≥29 (Group 3) weeks. Outcome measures included predischarge mortality and major neonatal morbidity.Results Overall survival to discharge was comparable for singletons 611/676 (90%) and multiples 273/299 (91%). Use of assisted reproductive technologies (47 vs. 4%), antenatal steroids (80 vs. 68%), and delivery by cesarean section (84 vs. 62%) were significantly higher (p < 0.001) in multiples while pregnancy induced hypertension (8.7 vs. 31.6%, p < 0.001) and maternal chorioamnionitis (31 vs. 41%, p < 0.01) were seen less commonly compared with singleton pregnancies. Survival was comparable between singletons and multiples except for a lower survival in multiples in Group 2 (81.7 vs. 92.4%, p = 0.007). Major neonatal morbidities were comparable for multiples and singletons in the overall cohort. Presence of hemodynamically significant patent ductus arteriosus (HsPDA) requiring treatment (88.9 vs. 72.5%), air leaks (33 vs. 14.6%, p = 0.02), NEC (30 vs. 14.6%, p = 0.04), and composite morbidity (86 vs. 66%, p = 0.031) were significantly higher in multiples in Group 1. A significantly higher incidence of HsPDA (68.1 vs. 52.4%, p = 0.008) was also observed in multiples in Group 2. Multiple pregnancy was not an independent predictor of an adverse outcome on regression analysis (OR: 0.685, 95% confidence interval: 0.629–2.02) even in GA ≤25 weeks.Conclusion Neonatal mortality and morbidity were comparable in our cohort of PT/VLBW singletons and multiple births, but preterm multiple births ≤25 weeks had a higher incidence of neonatal morbidity.Key Points
Keywords: multiple births; outcomes singleton; very low birthweight; morbidity